Scenarios for the energy transition : global experience and best practices (International Renewable Energy Agency, 2020)
Upgrading today's power systems to accommodate high shares of renewable energy, boost efficiency and cut climate-damaging emissions calls for imaginative, holistic energy planning. Scenario modelling has become an essential tool to lay the groundwork for clean, reliable, sustainable future energy systems. This report from the International Renewable Energy Agency (IRENA) presents a collection of over 50 practices from over 20 governments and technical institutions worldwide, dedicated to improving the use and development of long-term energy scenarios to guide the clean energy transition. It draws on discussions conducted through a Clean Energy Ministerial (CEM) campaign, Long-term Scenarios for the Energy Transition, along with the LTES Network, an IRENA extension covering non-CEM countries. Energy transitions involve complex and varying challenges for different countries and regions. Yet the climate goals of the Paris Agreement include urgent action to decarbonise global energy use. Over 25 events held in 10 different countries provided the platform to discuss the optimal use of long-term energy scenarios.